Pengembangan media pembelajaran flipbook digital - Fajriyatin Niâ€™mah , Ana; Yudiono, Udik; Afian, Affan (Jurnal Riset Pendidikan Ekonomi, 2024)
The purpose of this research is to develop learning media using digital flipbooks in economics subjects, especially the material of International Economic Cooperation Class XI SMA Negeri 6 Malang Â which is effective and feasible to use. The research method used is R&D (Research and Development) by obtaining research data to produce, develop and validate products with carries the ADDIE model proposed by Dick and Carey. This research uses the ADDIE model which consists of five stages, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The measurement used in this research is a Likert scale. Data from the study were obtained through a questionnaire validated by media experts, material experts, linguists, and student respondents. The results of this study indicate that this digital flipbook learning media is effective and feasible to use. The research data obtained with the feasibility level of media experts by 95%, material experts by 80%, linguists by 93%, and limited trials on students obtained a score of 93% with a total of 33 students.